2020
DOI: 10.35942/ijcfa.v2i2.141
|View full text |Cite
|
Sign up to set email alerts
|

Internal Controls and Credit Risk Among Commercial Banks Listed in Nairobi Securities Exchange, Kenya

Abstract: Inappropriate credit policies, as well as inadequate, limited institutional capacity by Kenya's financial sector, led to several of the banking institutions collapsing over what was termed as poor management of credit risks which resulted to increased amounts of loans that were not being serviced. The main aim of the research project was to establish the effects of internal controls on credit risk among the banks listed in NSE. The distinctive goals included to find out the influence of internal control, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A conceptual framework is a blend of wideranging notions explaining the correlation linking the dependent variable and independent variables (Agang & Njoka, 2020). The study conceptual framework showed the relationship between financial performance of listed commercial banks at the NSE, Kenya (dependent variable) as affected by components of credit risk management (Independent variables) which were loans-to-deposit ratio and nonperforming loan ratio.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A conceptual framework is a blend of wideranging notions explaining the correlation linking the dependent variable and independent variables (Agang & Njoka, 2020). The study conceptual framework showed the relationship between financial performance of listed commercial banks at the NSE, Kenya (dependent variable) as affected by components of credit risk management (Independent variables) which were loans-to-deposit ratio and nonperforming loan ratio.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Nguyen (2021) conducted a study on the relationship between internal control and credit risk-the case of commercial banks in Vietnam for the period of 2009-2018, The study reviewed that the agency problem is a statistically significant variable in the model. Agang and Njoka (2020) conducted a study on Internal Controls and Credit risk among Commercial banks listed in Nairobi Securities Exchange, Kenya. The study reviewed that risk assessment, control activities, monitoring and control environment have a positive and significant effect on credit risk among banking companies trading in Kenya.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The last section of the questionnaire required the respondents to choose an option that best described what their institution practiced determining how effective the components of an internal control system is in reducing risks in Zambian commercial banks. Studies (Haddad, 2016;Ogwiji & Lasisi, 2022;Agang & Njoka, 2020;Ho Tuan Vu, 2016;Olatunji, 2009;Umar & Dikko, 2018;Ofel et al, 2020;Nguyen, 2021) have shown that a relationship exist between components of an internal control system and risk minimization. Therefore, Multiple regression was used as an analytical tool to understand the relationship that exist journal-ems.com between the dependent variable (Risk reduction) and the independent variables which are the five components of an effective internal control system (control environment, risk assessment, control activities, information, and communication as well as monitoring activities).…”
Section: Challenges Faced By Zambian Commercial Banks In Internal Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…this include integrity, ethical values and competence of the management's and board of directors provide direction for the company (Joseph et al, 2015). Risk assessment component were evaluate using the aspects relating to risk detection, analyzing risk, and procedures of managing risk of a company to show a fair financial statement in conformity with international accounting standard (Agang & Njoka, 2020). Control activities are policies and procedures that help to reduce firm risk in order to achieve the set objectives (Whittington & Delaney, 2016).…”
Section: Introductionmentioning
confidence: 99%